2011
DOI: 10.1364/oe.19.020251
|View full text |Cite
|
Sign up to set email alerts
|

Quantum cascade laser based standoff photoacoustic chemical detection

Abstract: Standoff chemical detection with a distance of more than 41 feet using photoacoustic effect and quantum cascade laser (QCL) operated at relatively low power, less than 40 mW, is demonstrated for the first time. The option of using QCL provides the advantages of easy tuning and modulation besides the benefit of compact size, light weight and low power consumption. The standoff detection signal can be calibrated as a function of different parameters such as laser pulse energy, gas vapor concentration and detecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 16 publications
0
22
0
1
Order By: Relevance
“…Figure 4b shows the TNT absorption spectrum measured by the CO 2 laser scan with a corresponding absorption peak at 10.65 µm. Similarly, we use IPA vapor (0.13% volume) as a safer experimental substitute of the explosive, which has a strong absorption peak at around 7.9 µm [26]. The emission wavelength of the laser is set accordingly.…”
Section: Preliminary Work Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 4b shows the TNT absorption spectrum measured by the CO 2 laser scan with a corresponding absorption peak at 10.65 µm. Similarly, we use IPA vapor (0.13% volume) as a safer experimental substitute of the explosive, which has a strong absorption peak at around 7.9 µm [26]. The emission wavelength of the laser is set accordingly.…”
Section: Preliminary Work Reviewmentioning
confidence: 99%
“…We also evaluated and characterized PA signal and found that it is linearly dependent on laser optical power, chemical vapor density and 1/R where R is the radius with the target chemical as the center. For further details, the reader is encouraged to see our work reported in [26]. Based on these findings, we were able to determine and setup the right parameters for extending our work to the outdoor experiment as described in the following section.…”
Section: Preliminary Work Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical sources in the mid-infrared (mid-IR) wavelength range are important for applications including trace gas sensing, explosive detections, spectroscopy and free space communications [1][2][3][4]. Mid-IR quantum cascade laser (QCL) is in unique position to be utilized for these applications.…”
Section: Introductionmentioning
confidence: 99%
“…Presently, the usefulness of the laser spectroscopy approach is limited by the availability of convenient tunable sources in the spectroscopically important "fingerprint" region from 3 μm to 20 μm [1]. Recent measurements with QC-DFB (distributed feedback quantum cascade laser) lasers [2,3] have demonstrated the usefulness of these devices for highly selective real-time trace gas concentration measurements based on the absorption spectroscopy with the sensitivity of several ppb [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%